2023
DOI: 10.1002/leg3.184
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide association study of variation in cooking time among common bean (Phaseolus vulgaris L.) accessions using Diversity Arrays Technology markers

Abstract: Stored grains of common bean (Phaseolus vulgaris L.) develop the hard‐to‐cook trait (HTC), which is manifested in a prolonged cooking time, thereby imposing time and energy constraints. The objective of this study was to determine variation in cooking time among common bean genotypes and to identify single nucleotide polymorphism (SNP) markers associated with cooking time.Seeds of 222 common bean accessions sourced from Kenyan institutions were multiplied in the Jomo Kenyatta University of Agriculture and Tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…The genetic control of water uptake during soaking and cooking time has been investigated via diversity panels using genome‐wide association studies (GWAS) and biparental populations using quantitative trait locus (QTL) mapping (Bassett, Kamfwa, et al., 2021; Bassett, Katuuramu, et al., 2021; Berry et al., 2020; Cichy et al., 2015; Diaz et al., 2021; Garcia et al., 2011). These studies found genomic regions associated with water uptake and cooking time on every chromosome and identified candidate genes within these QTLs associated with cooking time (Berry et al., 2020; Martinez‐Manríque et al., 2011; Sadohara et al., 2022; Wahome et al., 2023). The candidate genes identified include enzymes that modify pectin solubility such as galacturan 1,4‐alpha‐galacturonidase, pectinesterase/pectin methylesterase, polygalacturonase, and pectate lyase, as well as enzymes that indirectly impact cell wall solubility such as peroxidase (synthesizes condensed tannins) and phytase (removes phytic acid).…”
Section: Introductionmentioning
confidence: 99%
“…The genetic control of water uptake during soaking and cooking time has been investigated via diversity panels using genome‐wide association studies (GWAS) and biparental populations using quantitative trait locus (QTL) mapping (Bassett, Kamfwa, et al., 2021; Bassett, Katuuramu, et al., 2021; Berry et al., 2020; Cichy et al., 2015; Diaz et al., 2021; Garcia et al., 2011). These studies found genomic regions associated with water uptake and cooking time on every chromosome and identified candidate genes within these QTLs associated with cooking time (Berry et al., 2020; Martinez‐Manríque et al., 2011; Sadohara et al., 2022; Wahome et al., 2023). The candidate genes identified include enzymes that modify pectin solubility such as galacturan 1,4‐alpha‐galacturonidase, pectinesterase/pectin methylesterase, polygalacturonase, and pectate lyase, as well as enzymes that indirectly impact cell wall solubility such as peroxidase (synthesizes condensed tannins) and phytase (removes phytic acid).…”
Section: Introductionmentioning
confidence: 99%
“…Phvul.008G019500 (MEI2-like 4) associated with a SNP at 1,633,220 bp in G19833 was a candidate for L* pod interior and a* pod exterior, and previously was identified as a candidate for flower, pod, and seed development [35,63]. Phvul.010G032700 (Sec23/Sec24 protein transport family protein) at 4,552,800-4,753,654 bp was a candidate for a*, b*, and C* pod exterior in G19833 and it was previously identified as being involved in the photosynthetic process as a response to water deficiency [63][64][65] (Table S1).…”
Section: Candidate Genes From Other Studiesmentioning
confidence: 99%
“…In a previous study consisting of 206 common bean accessions of the Andean Diversity Panel (ADP), several significant single nucleotide polymorphisms (SNPs) associated with CT were reported on Pv02, Pv03 and Pv06, respectively (Cichy et al, 2015). Additional evaluation of 430 accessions of the ADP resulted in identification of additional significant SNPs on Pv03, Pv04, Pv06, Pv07, Pv08 and Pv11 (Bassett et al, 2020), and on Pv10 using 220 accessions freshly harvested and stored for 4 months at 35 C and 50% RH for accelerating aging (Wanjohi et al, 2023). In another study, 10 QTLs were identified for CT in TZ-27 (slow cooking) and TZ-37 (fast cooking) recombinant inbred line (RIL) population on chromosomes Pv01, Pv02, Pv03, Pv05, Pv06, Pv10 and Pv11, and three QTLs, namely, CT3.1 on Pv03, CT6.1 on Pv06 and CT11.2 on Pv11, were stable across multiple environments (Berry et al, 2020).…”
Section: Introductionmentioning
confidence: 99%